Weaning Markedly Affects Transcriptome Profiles and Peyer’s Patch Development in Piglet Ileum - Inoue, Ryo; Tsukahara, Takamitsu; Nakatani, Masako; Okutani, Mie; Nishibayashi, Ryoichiro; Ogawa, Shohei; Harayama, Tomoko; Nagino, Takayuki; Hatanaka, Hironori; Fukuta, Kikuto; Romero-Pérez, Gustavo A.; Ushida, Kazunari; et al. (Frontiers in Immunology, 2015)
Transcriptome analyses were conducted on the ileal mucosa of 14-35 day-old piglets to investigate postnatal gut development during suckling and post-weaning. The transcriptome profiles of 14 day-old suckling piglets showed a considerably higher number of differentially expressed genes than did those of 21, 28 and 35 day olds, indicating an intensive gut development during the first 14-21 postnatal days. In addition, the analysis of biological pathways indicated that Chemotaxis Leucocyte chemotaxis was the most significantly affected pathway in suckling piglets between 14 and 21 days of age. Weaning negatively affected pathways associated with acquired immunity, but positively affected those associated with innate immunity. Interestingly, pathway Chemotaxis Leucocyte chemotaxis was found positively affected when comparing 14 and 21 day-old suckling piglets, but negatively affected in 28 day-old piglets weaned at 21 days of age, when compared with 28 day-old suckling piglets. Genes CXCL13, SLA-DOA (MHC class II), ICAM1, VAV1 and VCAM1 were involved in the pathway Chemotaxis Leukocyte chemotaxis and they were found to significantly change between 14 and 21 day-old suckling piglets, and between groups of suckling and weaned piglets. The expression of these genes significantly declined after weaning at 14, 21 and 28 days of age. This decline indicated that CXCL13, SLA-DOA, ICAM1, VAV1 and VCAM1 may be involved in the development of Peyer’s patches because lower gene expression clearly corresponded with smaller areas of Peyer’s patches in the ileal mucosa of piglets. Moreover, weaning piglets prior to a period of intensive gut development i.e., 14 days of age, caused significant adverse effects on the size of Peyer’s patches, which were not reverted even 14 days post-weaning.